A national questionnaire survey of Japanese urologists on active surveillance for low‐ and intermediate‐risk prostate cancer. (22nd November 2022) - Kato, Takuma; Tohi, Yoichiro; Honda, Tomoko; Matsuda, Iori; Osaki, Yu; Naito, Hirohito; Matsuoka, Yuki; Okazoe, Homare; Taoka, Rikiya; Tsunemori, Hiroyuki; Ueda, Nobufumi; Sugimoto, Mikio
Abstract : Objective: To conduct a national questionnaire survey of Japanese urologists on active surveillance (AS) for low‐ and intermediate‐risk prostate cancer (PCa). Methods: A questionnaire was sent to 922 Japanese Urological Association Teaching Base Hospitals. The items included were years of experience as a urologist, sex, workplace, treatment equipment owned, specialty area of daily practice, specialty area of urological cancer, and six hypothetical cases of AS. The cases were categorized by the following Gleason scores: 3 + 3 low risk of PCa, 3 + 4 intermediate risk, and 4 + 3 intermediate risk, with or without comorbidities for each case. Comorbidities were defined as cardiovascular diseases or illnesses warranting anticoagulant therapy. Results: Altogether, 1962 questionnaires were analyzed. Responses were almost equally distributed among all age groups. Workplaces included general hospitals (49.4%), university hospitals (40.3%), and cancer centers (4.2%). Percentages of proposed AS for low risk/no comorbidity, low risk/with comorbidity, intermediate‐risk 3 + 4/no comorbidity, intermediate risk 3 + 4/with comorbidity, intermediate risk 4 + 3/no comorbidity, and intermediate risk 4 + 3/with comorbidity were 90.5%, 90%, 39.5%, 48.7%, 15%, and 22%, respectively. Analysis of the correspondents' backgrounds showed that the more the urologists' years of experience, the less they were to advise AS of low‐risk patients. In the presence of comorbidities, urologists across all age groups tended to propose AS, even in the same Gleason grade group. Cancer center urologists recommended AS more often than their counterparts at general and university hospitals. Conclusions: Approximately 40% of urologists proposed AS for intermediate‐risk cases, confirming that AS for intermediate‐risk patients is being considered in Japan.